Competency of Academic Nurse Educators. (October 2020) - Satoh, Miho; Fujimura, Akiko; Sato, Naoko
Background: In the face of a rapidly changing social environment and increasing demand for health care services, there is a global concern that academic nurse educators should have expert-level competencies and should improve the level of nursing education. Objective: This study aimed to investigate the elements that constitute competency in academic nurse educators. Methods: A cross-sectional self-completed online survey was conducted involving academic nurse educators working at universities in Japan. We invited 277 nursing universities to participate in the survey and to provide academic nurse educators with information about the research by contacting the dean of each university's nursing department. In total, 372 educators completed the survey (response rate 4.03%), and after excluding those with incomplete data, 367 were analyzed (valid response rate 3.97%). The data were analyzed by exploratory-factor analysis, with the least-squares method and promax rotation performed. Results: An exploratory analysis yielded five competency factors: "facilitating active learning, " "engaging in academic research activities, " "participating in university management, " "undertaking self-directed learning based on professional ethics, " and "practicing education autonomously." Conclusions: The competencies identified in the present study are essential for academic nurse educators, and the five factors are in accord with the findings of previous studies. Support systems for academic nursing educators should be established to improve their competencies comprehensively. However, further research is needed to develop the competencies of academic nurse educators into more comprehensive and sophisticated competencies.